NT3-chitosan enables de novo regeneration and functional recovery in monkeys after spinal cord injury - Rao, Jia-Sheng (Proc Natl Acad Sci U S A, 2018)
Spinal cord injury (SCI) often leads to permanent loss of motor, sensory, and autonomic functions. We have previously shown that neurotrophin3 (NT3)-loaded chitosan biodegradable material allowed for prolonged slow release of NT3 for 14 weeks under physiological conditions. Here we report that NT3-loaded chitosan, when inserted into a 1-cm gap of hemisectioned and excised adult rhesus monkey thoracic spinal cord, elicited robust axonal regeneration. Labeling of cortical motor neurons indicated motor axons in the corticospinal tract not only entered the injury site within the biomaterial but also grew across the 1-cm-long lesion area and into the distal spinal cord. Through a combination of magnetic resonance diffusion tensor imaging, functional MRI, electrophysiology, and kinematics-based quantitative walking behavioral analyses, we demonstrated that NT3-chitosan enabled robust neural regeneration accompanied by motor and sensory functional recovery. Given that monkeys and humans share similar genetics and physiology, our method is likely translatable to human SCI repair.